The impact of allogeneic hematopoietic cell transplantation on the mortality of poor-risk non-Hodgkin lymphoma: an intent-to-transplant analysis - Selberg, Lorenz; Stadtherr, Peter; Dietrich, Sascha; Tran, Thuong Hien; Luft, Thomas; Hegenbart, Ute; Bondong, Andrea; Meißner, Julia; Liebers, Nora; Schmitt, Michael; Ho, Anthony Dick; Müller-Tidow, Carsten; et al. (Bone marrow transplantation, 2021)
Purpose of this single-centre retrospective study was to assess the outcome of allogeneic hematopoietic cell transplantation (alloHCT) for relapsed/refractory (r/r) non-Hodgkin lymphoma (NHL) by intent-to-transplant (ITT). Included were all consecutive patients with diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), mantle cell lymphoma (MCL), and peripheral T-cell lymphoma (PTCL) for whom a donor search was performed between 2004 and 2018. Primary endpoint was overall survival (OS) measured from search initiation. A donor search was initiated for 189 patients (DLBCL 61, FL 32, MCL 43, and PTCL 53), with 76% of the patients having active disease. OS at 5 years after search initiation for DLBCL, FL, MCL, and PTCL was 26%, 44%, 52%, and 50%, respectively. AlloHCT was performed in 137 patients (72%; DLBCL 64%). Main reason for not undergoing alloHCT was disease progression, whereas donor unavailability accounted for only 4% of pretransplantation failures. These results suggest that survival of patients with r/r NHL entering the alloHCT route may be overestimated by a factor of 1.2-1.4 if based on actually transplanted patients only. This effect should be taken into account when using alloHCT as benchmark for new therapeutic approaches for the treatment of poor-risk NHL.